Konsep Diri Mahasiswi Penggemar NCT pada Program Studi Pendidikan Sosiologi Fakultas Keguruan dan Ilmu Pendidikan Universitas Sultan Ageng Tirtayasa - Siti Rohaliya (Jurnal Neo Societal, 2026)
This study was conducted to find and observe the formation of self-concept in female fans of the boyband NCT, especially in the Sociology Education environment of the Faculty of Teacher Training and Education, Untirta. The purpose of the study was to determine the process of self-concept formation of female Sociology Education as fans of the K-Pop boyband at the Faculty of Teacher Training and Education, Untirta. The method used in this study is phenomenology, which is a type of qualitative research. The approach is by listening and observing more closely and in detail regarding individual understanding and explanations of their experiences. The results of this study show that, in the thinking process (Mind), a music and MV from the boyband NCT is a language gesture that can evoke responses according to the meaning of the lyrics conveyed in the song and MV. When being me (I), NCT boyband fans will respond spontaneously to people who give negative responses to the boyband NCT. When NCT fans become me (Me), they think about the consequences. Female NCT fans are part of the FKIP Untirta society (Society) who interact with each other. The conclusion of the research by Sociology Education Students of Boyband NCT (Neo Culture Technology) Fans at the Faculty of Teacher Training and Education, Sultan Ageng Tirtayasa University, researchers saw that self-concept is no longer only formed by the physical environment, but is also significantly influenced by the virtual environment and digital social interactions